Fintech Technology Strategy for Financial Management of PT Astra Indonesia Company - Daming , Sudirman; Widyawati, Widyawati (STIE Amkop Makassar, 2023)
Study This aiming For analyzing fintech technology strategies and their impact to management finance at PT Astra Indonesia. In the increasingly digital era advanced , fintech has appear as solution important For increase efficiency operational , transparency , and decision making decision data -based in the company . Through implementation of fintech, PT Astra Indonesia succeeded increase efficiency of financial processes , which contributes to the management more cash flow good . Access to real-time data allows management For make more decisions​ fast and accurate , and minimize risk lack liquidity . In addition , fintech also strengthens transparency and internal control , which in turn reduce potential abuse and increase integrity report finance . However , the challenge in implementation technology this , like resistance culture employees and concerns about data security , need overcome For maximize benefits of fintech. Research This conclude that although there is obstacles , the implementation of fintech at PT Astra Indonesia provides impact significant positive​ to management finance , making company more adaptive and competitive in an increasingly competitive market dynamic . In general overall , results study This show that fintech strategies can become effective tool​ For increase management finance , with condition existence support from all parties in​ company as well as effort sustainable For overcome existing challenges .​